Prolonged suppression of neuropathic hypersensitivity upon neurostimulation of the posterior insula in mice - Li, Han; Gan, Zheng; Wang, Lirong; Oswald, Manfred; Kuner, Rohini (Cells, 2022)
Neurostimulation-based therapeutic approaches are emerging as alternatives to pharmacological drugs, but need further development to optimize efficacy and reduce variability. Despite its key relevance to pain, the insular cortex has not been explored in cortical neurostimulation approaches. Here, we developed an approach to perform repetitive transcranial direct current stimulation of the posterior insula (PI tDCS) and studied its impact on sensory and aversive components of neuropathic pain and pain-related anxiety and the underlying neural circuitry in mice using behavioral methods, pharmacological interventions and the expression of the activity-induced gene product, Fos. We observed that repetitive PI tDCS strongly attenuates the development of neuropathic mechanical allodynia and also reverses chronically established mechanical and cold allodynia for several weeks post-treatment by employing descending opioidergic antinociceptive pathways. Pain-related anxiety, but not pain-related aversion, were inhibited by PI tDCS. These effects were associated with a long-term suppression in the activity of key areas involved in pain modulation, such as the cingulate, prefrontal and motor cortices. These data uncover the significant potential of targeting the insular cortex with the objective of pain relief and open the way for more detailed mechanistic analyses that will contribute to improving cortical neurostimulation therapies for use in the clinical management of pain.
Gesehen am 21.12.2022